2013
DOI: 10.1016/j.febslet.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of productive binding modes in the human chitotriosidase

Abstract: a b s t r a c tHuman chitotriosidase (HCHT) is a family 18 chitinase that is an innate part of the immune system. We have mapped preferred productive binding modes of chito-oligosaccharide substrates to HCHT and the data show that HCHT has strong binding affinity in the +3 subsite. Moreover, HCHT shows anomer-specific binding affinities in subsites +2 and +3. These features could endorse HCHT with higher endo-activity and a higher transglycosylation potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Ec Chi1 synthesized long-chain CHOS even with low concentrations of substrate and enzyme. Amino acid residues positioned at acceptor binding site are assumed to be crucial for TG activity 43 . The known chitinases with TG activity were occupied with aromatic amino acids at +n subsites.…”
Section: Discussionmentioning
confidence: 99%
“…Ec Chi1 synthesized long-chain CHOS even with low concentrations of substrate and enzyme. Amino acid residues positioned at acceptor binding site are assumed to be crucial for TG activity 43 . The known chitinases with TG activity were occupied with aromatic amino acids at +n subsites.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Tryptophan is known to be involved in stacking interactions with sugar in the active site of carbohydrate active enzymes (Eide et al 2013 ; Larsson et al 2006 ). Most likely, there is a combination of factors in the structure of AnMan5B that contribute to high transglycosylation capacity, where R206, analogous to R171 in TrMan5A, might play one of the roles in providing affinity in the aglycone subsites, potentially together with W242.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme was initially thought to be an exochitinase because it can hydrolyze chitotriose residues and was termed chitotriosidase based on this observation. However, recent structural and binding modes studies revealed the enzyme to be more of an endochitinase rather than an exochitinase [ 29 , 30 ]. Furthermore, the strong binding affinity of chitotriosidase to its substrate is also responsible for the relatively high transglycosylation activity of the enzyme even in the absence of excess substrate concentrations, making chitotriosidase a complete independent chitinolytic machinery, and this is in accordance with its anticipated physiological role as a potent immunological defense weapon against microorganisms containing chitin [ 31 , 32 ].…”
Section: Chemistry and Modes Of Actionmentioning
confidence: 99%